Technology-based health promotion - Bull, Sheana; McFarlane, Mary.; Sage eBooks (Los Angeles, [Calif.] ; London : SAGE, 2011)
Designed for courses in health promotion, public health, health science, and social science, this book examines the role that technology can play in the promotion of health and the prevention of disease.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Medical informatics; Health promotion; Health Promotion -- trends; Cellular Phone -- trends; Medical Informatics Applications; Program Evaluation -- trends; Electronic books